The Use of Team-Based Learning as a Diagnostic Tool in the Chemistry Teaching-Learning - Nairley Cardoso Sá Firmino; Antônio Mateus Paiva Salustiano; Diego Farias Firmino; Luciana Rodrigues Leite (Revista Brasileira de Pesquisa em Educação em Ciências, 2020)
Team-Based Learning (TBL) is a teaching strategy developed in phases — the pre-class, the guarantee of preparation, and the application of concepts — which proposes to break with traditionalism in the classroom. In this essay, TBL was used as a diagnostic tool for the learning of students. One hundred and twenty-seven students from the Dentistry course of a University Center in Ceará enrolled in the Chemistry module participated in this study. They were divided into three classes (two regular and a special one, composed of the repeaters students) and participated in two stages: preparation and guarantee of preparation. To systematize the activities, initially, the students were instructed to study at home, with the didactic material previously provided (pre-class). The second stage, consisting of individual, collective tests and feedback from the professor, had the data categorized and analyzed, in association with the narrative of the students. There was an improvement in the comprehension of the students after the collective work, the difficulties were higher in the content of intermolecular forces, and the special class expressed the need for directed pedagogical support. It was concluded that the use of TBL as a diagnostic mechanism is feasible, once it provides a complete visualization of the educational process and assists in directing the teaching work. Besides, this essay contributes to the professor training, once it increases the possibilities of using TBL at the university level and corroborates for the educators to recognize it as an adjunct of the pedagogical work, entirely. Finally, the innovative character of this study is reiterated, since similar publications were not, yet, identified in the literature of the area.